The Landscapes of Winnipeg's Wildwood Park - Martin, Michael (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2001)
This paper is a review of the history of the differentiated landscapes of Winnipeg's Wildwood Park—their origins and their transformations since the community's establishment in the late 1940s by builder/developer Hubert Bird. Bird patterned his scheme after Stein and Wright's Radburn garden-city fragment, but the uniquely evolved character of Wildwood Park owes as much to regional landscape, geomorphology, and local post-war culture as it owes to its famed antecedent. As a unique and idiosyncratic community design, Wildwood Park merits attention and further study by planning historians and those interested in alternative neighbourhood forms as social constructions or cultural landscapes. In addition, it suggests many things to designers of contemporary communities, many of whom are currently looking to traditional pre-World-War-II grid-pattern neighbourhood structure and aesthetics as inspiration for (presumably) more socially cohesive neighbourhoods. Whether such designers are inclined toward the garden-city precept for separation of automobiles and pedestrians, or toward this contradictory "new urbanist" premise that cars and people should cohabitate within community open space, Wild-wood Park has much to offer as precedent. Both its pedestrians-only park and its highly interactive lanes that do mix people and cars—and particularly these two complementary landscapes considered as a "matched set"—offer many interesting design lessons in matters of two-dimensional platting, three-dimensional neighbourhood structure and four-dimensional considerations for structural and landscape transformations that occur over the span of several decades.